Management of traumatic dental injuries in the permanent dentition - Krastl, Gabriel; Weiger, Roland; Filippi, Andreas; Ebeleseder, Kurt A.; Galler, Kerstin Martina (John Wiley and Sons Ltd, 2022)
In the permanent dentition, most traumatic dental injuries (TDI) result in crown fractures and minor luxation injuries. After crown fractures, reattachment of the coronal fragment is a conservative approach to re-establish function and aesthetics. As an alternative, resin composites can be used on a routine basis for a minimal invasive restoration of fractured teeth. When the pulp of a previously intact tooth is traumatically exposed, it can generally be assumed that the pulp is healthy and capable of regeneration. Vital pulp treatment is the treatment of choice and has high success rates. The treatment of crown-root fractures is challenging, requiring consideration of periodontal, endodontic, and, in particular, restorative factors. Teeth with crown-root fractures in proximity to the marginal bone level may be saved following surgical crown lengthening, orthodontic extrusion, or surgical extrusion.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Crown-root fractures; Dental trauma; Intra-alveolar root fractures; Luxation injuries; Permanent dentition; Splinting; Systemic doxycycline administration; Tetanus status; Traumatic dental injuries